Novos resultados sobre a estabilidade e controle de sistemas nao-lineares utilizando modelos fuzzy e LMI - Teixeira, Marcelo Carvalho Minhoto [UNESP]; Pietrobom, Hilton Cleber; Assunção, Edvaldo [UNESP] (My University, 2000)
Relaxed conditions for the stability study of nonlinear, continuous and discrete-time systems given by fuzzy models are presented. A theoretical analysis shows that the proposed method provides better or at least the same results of the methods presented in the literature. Digital simulations exemplify this fact. These results are also used for the fuzzy regulators design. The nonlinear systems are represented by the fuzzy models proposed by Takagi and Sugeno. The stability analysis and the design of controllers are described by LMIs (Linear Matrix Inequalities), that can be solved efficiently by convex programming techniques. The specification of the decay rate, constraints on control input and output are also described by LMIs. Finally, the proposed design method is applied in the control of an inverted pendulum.
Keywords: Computer simulation; Control system analysis; Control system synthesis; Fuzzy control; Fuzzy sets; Mathematical models; Matrix algebra; Nonlinear control systems; System stability; Linear matrix inequalities (LMI); Discrete time control systems